Intensive care unit team perception of palliative care: the discourse of the collective subject - Juliana El Hage Meyer de Barros Gulini; Eliane Regina Pereira do Nascimento; Rachel Duarte Moritz; Luciana Martins da Rosa; Natyele Rippel Silveira; Mara Ambrosina de Oliveira Vargas
Abstract OBJECTIVE To learn the perception of health professionals in an intensive care unit towards palliative care. METHOD This was a descriptive and qualitative study based on the converging care approach conducted at an intensive care unit in the South of Brazil. Semi-structured interviews were used to investigate the understanding of the professionals about palliative care in this unit. The data were organized and analyzed using the discourse of the collective subject method with the help of Qualiquantisoft® software. RESULTS Participants included 37 professionals (12 nurses, 11nursing technicians, 5 physical therapists and 9 doctors). The key ideas extracted from the interviews were: care in the end stage of life that avoids futile measures; comfort care; lack of standardized care and lack of team training. CONCLUSION The professionals perceived palliative care as appropriate in the last stages of life, with no need for futile treatment or as comfort measures. However, they are aware of the lack of standardization and lack of capacity building in this area, which leads them to conceive palliative care as terminal care, and measures are recommended to break with this stigma.